2020
DOI: 10.1128/mbio.02410-20
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Genomes Survive Mitosis via the IE19 Chromatin-Tethering Domain

Abstract: The genomes of DNA tumor viruses regain nuclear localization after nuclear envelope breakdown during mitosis through the action of a viral protein with a chromatin-tethering domain (CTD). Here, we report that the human cytomegalovirus (HCMV) genome is maintained during mitosis by the CTD of the viral IE19 protein. Deletion of the IE19 CTD or disruption of the IE19 splice acceptor site reduced viral genome maintenance and progeny virion formation during infection of dividing fibroblasts, both of which were resc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 75 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…Their data also suggest that viral major immediate-early (IE) proteins of the IE1 family contribute to HCMV episome tethering. These findings are consistent with two other recent reports implicating IE1 family proteins in viral genome maintenance ( Tarrant-Elorza et al., 2014 ; Lyon et al., 2020 ). A role for IE1 in maintaining HCMV latency may come as a surprise, since the major IE promoter-enhancer (MIEP) appears to be highly repressed during latency in myeloid cells including monocytes ( Elder and Sinclair, 2019 ; Dooley and O’Connor, 2020 ).…”
Section: Host Interactions During CMV Latency and Reactivationsupporting
confidence: 93%
“…Their data also suggest that viral major immediate-early (IE) proteins of the IE1 family contribute to HCMV episome tethering. These findings are consistent with two other recent reports implicating IE1 family proteins in viral genome maintenance ( Tarrant-Elorza et al., 2014 ; Lyon et al., 2020 ). A role for IE1 in maintaining HCMV latency may come as a surprise, since the major IE promoter-enhancer (MIEP) appears to be highly repressed during latency in myeloid cells including monocytes ( Elder and Sinclair, 2019 ; Dooley and O’Connor, 2020 ).…”
Section: Host Interactions During CMV Latency and Reactivationsupporting
confidence: 93%
“…Furthermore, hIE1 has been shown to contain a C-terminal chromatin tethering domain (CTD) that plays a role in association with mitotic chromosomes [ 25 , 26 , 39 ]. Immunofluorescence analyses revealed that rIE1 could neither bind to rats nor human mitotic chromatin ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the CTD is dispensable for productive replication in asynchronous fibroblast cells [ 8 , 25 ]. However, as suggested by a recent publication using a CTD-deficient recombinant in the Towne strain of HCMV, this domain may be important for maintaining the viral genome during mitosis [ 39 ]. If the CTD of hIE1 indeed acts as a genome maintenance factor, one may speculate that either RCMV lacks this function or encodes a different protein that serves to maintain viral genomes during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the IE protein facilitates the correct nuclear localization of the CMV genome during mitosis through the chromatin-tethering domain. The IE protein can also maintain the mitotic cell cycle of the host cells and induce cell proliferation [ 41 ]. In addition, CMV expresses the US28 protein, which induces IL-6 expression and STAT3 phosphorylation, both promoting paracrine signaling in oncogenesis [ 42 ].…”
Section: Mechanisms Of Cmv-related Glioma Tumorigenesismentioning
confidence: 99%